The role and importance of tactical competence in executing operational tasks within the organization of the state’s security and defense sector - Hydenko, Yevhen (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article explores the importance of tactical competence in the effective execution of operational and combat tasks within the organization of the security and defense sector of the state. Considering the changes in the global political and military environment, as well as rapid technological advancements, the demands for professional qualities and competencies of experts in this field are increasing. Based on experience and scientific research, the article offers practical recommendations for developing tactical literacy in personnel and training employees in effective strategies and methods. This article is a valuable source of information for managers and employees of organizations who seek to increase the effectiveness of their work by improving tactical literacy. Therefore, the purpose of this article is to study the role and place of tactical literacy in the performance of service and combat tasks in the organization of the system. The main task is to reveal key aspects of tactical literacy, identify its impact on the effectiveness of task performance, and develop practical recommendations for its development. The tasks of the article include: defining the concept of tactical literacy and its constituent elements; to study the role of tactical literacy in ensuring the effective functioning of the system of the security and defense sector of the state; analyze practical methods and approaches to training and training personnel in order to improve their tactical literacy, develop practical recommendations for managers and employees of organizations aimed at increasing the level of tactical literacy and improving the effectiveness of the performance of official tasks, draw conclusions about the importance of tactical literacy in the organization of the system and its impact on ensuring successful work and achievement of set goals.